Mauqif ‘Abd al-Qāhir al-Jurjānī min al-Naẓm al-Qur’ānī - Noraffendie, Muhammad Nur Afiq Aiman Md.; Nasir, Mohd Shahrizal (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2024)
This research deals with a study of ‘Abd al-Qāhir al-Jurjānī’s perspective on Qur’anic Nazm, which makes it a basis for understanding the beauty of the eloquence of the Holy Qur’an. The research has shown that ‘Abd al-Qāhir al-Jurjānī made a qualitative shift in his study of grammar, as he gave priority to meaning over words, and considered that grammar has an interconnected relationship between words and meanings that must be considered according to the rules of grammar, which achieves an impact on the soul of the listener. The nature of the research necessitated the use of the descriptive analytical method by collecting and analyzing data from primary sources such as Dalāʾil al-Iʿjāz and al-Risālah al-Shāfiyyah comparing ‘Abd al-Qāhir al-Jurjānī’s vision with the some of previous scholars’ opinions who contributed to developing this idea. The research also discussed ‘Abd al-Qāhir al-Jurjānī’s criticism of the Ṣarfah theory, which denies Nazm as an aspect of the Qur’anic miracle. The findings underscore that ‘Abd al-Qāhir al-Jurjānī raised Nazm to a new level, that the Holy Qur’an is miraculous with its Nazm due to the strong correspondence between meanings, words, and grammar, which constitutes a unique Nazm that humans can never match. The research results highlight ‘Abd al-Qāhir al-Jurjānī’s contribution in employing grammar and rhetoric to understand the aesthetic aspects of Nazm, which enriches rhetorical and interpretive studies in Islamic heritage.